An Investigation of Critical Thinking Skills of Pre-Service English Teachers in The Context of Phonological Acquisition - Rima, Rosmania; Muhyidin, Asep (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The objective of this study was to investigate the critical thinking abilities of pre-service English teachers in the context of phonological acquisition. The present study employed a quantitative descriptive approach, which included a sample of 25 pre-service English teachers in the sixth semester at the Teachers Training Faculty in Serang, Banten. The research employed a critical thinking skill assessment instrument with essay question formats, which aligned with Ennis' five indications of critical thinking skills. The findings indicated that the critical thinking abilities of pre-service English teachers were classified as low to moderate across the five parameters. There is a need for enhancement in the realm of lecture activities in order to foster the development of critical thinking abilities among pre-service English teachers.